Immunotherapy for multiple myeloma. Issue 1 (February 2014) - Rosenblatt, Jacalyn; Bar-Natan, Michal; Munshi, Nikhil C; Avigan, David E
Abstract : The potential potency of the immune system in targeting malignant plasma cells in multiple myeloma is best demonstrated in the allogeneic transplant setting, where durable responses can be achieved. However, allogeneic transplantation is associated with significant morbidity and mortality related to graft versus host disease, due to the non-specific nature of allo-reactive T cell responses mediated by donor lymphocytes. Immunotherapeutic approaches that more specifically target the malignant plasma cells have the potential to improve outcomes in multiple myeloma. The development of clinically efficacious immunotherapy in multiple myeloma is dependent on achieving a greater understanding of the complex interactions between the immunologic milieu and the growth of the malignant plasma cell clone. A number of antigens have been identified on malignant plasma cells that may be targeted by both humoral and cell mediated immunotherapeutic strategies. Encouraging results have been demonstrated both pre-clinically and in clinical trials. In this review, we summarize the clinical data evaluating immunotherapeutic approaches for the treatment of multiple myeloma.